Entry Characteristics and Participation in a Peer Learning Program as Predictors of First-Year Students' Achievement, Retention, and Degree Completion - Jacques van der Meer; Rob Wass; Stephen Scott; Jesse Kokaua (SAGE Publishing, 2017)
Success in the first year of higher education is important for students' retention beyond their first year and for completion of their undergraduate degree. Institutions therefore typically front-load resources and interventions in the first year. One such intervention is the Peer Assisted Study Sessions (PASS) program. This program is known in the United States as Supplemental Instruction. It provides first-year students with an opportunity to learn study skills in the context of a particular unit of study (course/module). In this article, we consider the relationship between students' prior academic achievement and participation in the PASS program, as well as the impact of participation on first-year students' first-year grade point average, retention, and degree completion. The findings suggest that PASS does not just attract academically high-achieving students and that participation in it contributes to students' academic achievement in their first year, retention beyond the first year, and completion of an undergraduate degree.